Gastric adenocarcinoma: 1-year overall survival, disability-adjusted life years, years of life lost, and prognostic factors—a single-institution experience - Tiengo, Tatiane; Fernandes, Gisele Aparecida; Curado, Maria Paula (Frontiers in Oncology, 2022)
Objective: To analyze factors affecting 1-year overall survival and burden of Gastric Adenocarcinoma in a single institution cohort. Methods: A prospective cohort study of Gastric Adenocarcinoma patients from a cancer center in São Paulo, Brazil, were recruited between February 2016 and July 2019. Overall survival was analyzed at 12 months post-diagnosis using the Kaplan-Meier method. A logrank test was applied to compare curves. Sociodemographic and clinicopathological features were assessed to detect prognostic factors using univariate and multivariable Cox regression to calculate Hazard Ratio (HR) and its confidence intervals (CI). Disability-adjusted life years (DALY) constituted the sum of years of life lost (YLL) plus years lived with the disability (YLD). YLL represented the sum of years lost before the age of 76.6 years. YLD was calculated as the number of cases multiplied by the duration and burden of the disease. YLL per death was calculated as mean YLL for each individual. Results: Overall survival at 1-year follow-up was 80.8%. The multivariable model adjusted for age and sex identified cerebrovascular disease (HR 8.5, 95% CI 3.3–21.8), stages III/IV (HR 5.7, 95% CI 2.3–13.7), diabetes (HR 3.2, 95% CI 1.5–6.6), and <9 years education (HR 2.9, 95% CI 1.5–5.8) as prognostic factors. Out of the 214 treated cases, there were 700.72 DALYs during the first year, of which 90.55% corresponded to YLL and 9.45% to YLD. Average YLL per death was 15.48, and was higher among females (19.24 YLL per death). Conclusion: At a single cancer center, one year overall survival probability was around 80% in patients with Gastric Adenocarcinoma. Patients with higher risk of death had cerebrovascular disease, advanced clinical staging, diabetes, and/or lower educational level. Around 700 years of DALY were documented, with females having the highest YLL per death. Because this study was conducted at a single cancer center, the results might not be representative of a general population. To the best of our knowledge, this study was the first to assess Gastric Adenocarcinoma DALY, YLL, and YLL per death at the first year follow-up in a hospital cohort in Brazil.